2017
DOI: 10.1111/jfpp.13416
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of chia (Salvia hispanica L.) seed oil nanoemulsions using different emulsifiers

Abstract: In this study, the quality of spiral cold press chia seed oil was evaluated and four types of O/W chia seed oil nanoemlusion systems were prepared, including chia seed oil nanoemulsion stabilized with Tween 80 and Span 80 by spontaneous emulsification and microfluidization, sodium caseinate by microfluidization, and sucrose monopalmitate by microfluidization. All these optimized samples exhibited good storage stability for at least two weeks when stored at 4 8C or ambient temperature. The nanoemulsion stabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Since these particles are PL-based, we would suggest that they are multilamellar in nature, as has been previously demonstrated for other PL-based NL [31]. There is little information in the literature on the use of chia lipid fractions in nanotechnology [15,27]. Here, we show the possibility of preparing chia NE using only chia-derived lipids and PL residue as emulsifier.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Since these particles are PL-based, we would suggest that they are multilamellar in nature, as has been previously demonstrated for other PL-based NL [31]. There is little information in the literature on the use of chia lipid fractions in nanotechnology [15,27]. Here, we show the possibility of preparing chia NE using only chia-derived lipids and PL residue as emulsifier.…”
Section: Discussionsupporting
confidence: 65%
“…In view of the interest of PUFA-rich chia seeds and their bioactivities, our goal in this study was to obtain and characterize chia seed lipids, focusing on phospholipid fraction, and to investigate their use in the formulation of nanoemulsions (NE) and nanoliposomes (NL). Studies have reported the use of chia seed lipid fraction for the formulation of microemulsions using various materials as emulsifier and different microcapsule wall techniques [19][20][21][22][23][24][25][26], but little information is available on the use of ALA-rich chia seed lipids in nanosized particles [15,27]. Here, we demonstrate the feasibility of using chia seed lipids for preparing stable NL and NE, nanocarriers that have potential uses in both prevention and therapeutic applications.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The NEs prepared with sucrose monopalmitate showed best transparency with droplet diameter ca. 47 nm (Teng et al 2018). Blended cloves/cinnamon EO NEs fabricated using Tween 80 surfactant and ethanol (cosurfactant) with oil to the mixed surfactant/cosurfactant ratio of 1:9 showed higher antimicrobial activity against E. coli, B. subtilis, S. typhimurium, and S. aureus, even at far lower concentrations than free EOs and this NE could be applied as a natural antimicrobial agent in food industry (Zhang et al 2017).…”
Section: Nanoemulsions Of Essential Oils and Their Constituentsmentioning
confidence: 98%
“…For example, microfluidization mechanism eases the development of the stable nanoemulsion with the particle size ,160 nm. 39 The mechanism involves forcing the coarse emulsion through microchannels to the particular area by pneumatically powered pump by pressurizing compressed air up to about 150 MPa which results in nanoemulsion, 35,40 and the different passes lead to different sizes. It is also an easy-to-use and effective method for the development of other stable nanodelivery systems.…”
Section: Microfluidizationmentioning
confidence: 99%